Epidural Morphine or Butorphanol Augments Bupivacaine Analgesia During Labor. Issue 3 (May 1989) - Abboud, T. K.; Reyes, A.; Richardson, M.; Afrasiabi, A.; D'onofrio, L.; Kalra, M.; Zhu, J.; Khoo, N.; Cheung, M.; Mantilla, M.; Mosaad, P.; Paul, R.
Abstract : To determine the efficacy and the safety of epidural morphine or butorphanol combined with bupivacaine, 40 healthy parturients were studied during labor and delivery. All patients received an epidural test dose of 2 ml of 0.5% bupivacaine. Patients were then randomly assigned to receive one of four epidural regimens in a double-blind fashion: 0.25% bupivacaine + 1 mg butorphanol (Group I), 0.25% bupivacaine + 2 mg butorphanol (Group II), 0.25% bupivacaine + 2 mg morphine (Group III), or 0.25% bupivacaine alone (Group IV). Each group consisted of ten patients. All subsequent epidural injections were with plain 0.25% bupivacaine. Duration of analgesia was significantly longer for groups I, II, and III when compared to group IV ( p ≤ .01); 139 ± 111, 141 ± 14, 199 ± 29, and 96 ± 6 minutes, X ± SEM respectively. Quality of analgesia was significantly better in groups I, II, and III when compared with group IV. There were no differences between groups in duration of first and second stages of labor, uterine activity, or method of delivery. Thirty percent of patients in the morphine group (group III) developed mild pruritus that did not require any treatment. All neonates were vigorous at 5 minutes and had good Apgar Scores, umbilical cord acid base status, and Neurological Adaptive Capacity Scores. The authors conclude that adding small doses of either morphine or butorphanol to epidural bupivacaine during labor is effective and safe. Butorphanol may be preferable since none of the patients experienced pruritus.